A wearable foot motion tracking sensor for outdoor running - Low, J.-H.; Lim, P.-Y.; Yeow, C. H. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Throughout human history, running has evolved from a form of locomotion to a recreation or competitive pursuit. The purpose of this project was to develop a foot motion tracking sensor using inertial measurement unit (IMU) to determine the running kinematics of the ankles of individuals under different external or physical conditions such as change in directions, running on slopes or level ground or fatigue. These results may be helpful in providing a real-time quantitative data, which will be useful for runners to monitor their training programs and routes. The preliminary results showed that the system can detect ankle dorsiflexion/plantarflexion across different route condition, where these results can be used for further analysis such as designing a training program and monitoring the fatigue level.